Correlation Between the Level of Socio-economic Development and the Use of the Information and Communication Technologies - Rodionova, Irina A.; Mizerovskaya, Uliana V. (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
During recent decades, the rate of structural shifts in the world economy has been especially fast. One of the factors used to influence these processes was to actively develop hi-tech industries and information and communication technologies. With the course of time, the level of informatization of society becomes a defining factor for a country’s competitiveness and predefines its ability to integrate into the global economy. The article characterizes the readiness of different countries to make a move to an innovative way of development based on analysis of combined rating tables that contain integral indices of society’s informatization level. The level of accomplishment of the task to form an innovative type of economy can be assessed in the link between implementation of science and technology progress achievements (i.e.: through the use of information and communication technologies) and the level of socio-economic development of the world countries. Current positions held by Russia and Poland according to some integral indices are also being analyzed.